Behavioral Development and Career Character Thought Guidance and Counseling in Industrial Zone 4.0 - Paisal Manurung; Mudjiran Mudjiran; Neviyarni Neviyarni; Herman Nirwana (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The purpose of this article is to describe the development and career character as the human being is the social creatures, they can survive by socializing with the environment, society and their natural surroundings. Industrial Zone 4.0 has brought many behavioural and career changes that cannot be ruled out by anyone. This has given many problems and challenges to counsellor practitioners to provide diverse aspirations and motivations to the wider community. These problems and challenges include the low attitude of mutual help to help one another, the high rate of mutual prejudice to others, the lack of honesty for the achievement of desired goals, the high behaviour of crime. So, it is hoped that counsellors will continue to improve the basic knowledge of human needs and services in the Industrial Zone 4.0.